STRUKTUR DAN ANATOMI ORGANISASI - Muktar Asroni; Sukatin Sukatin; Zul Qarnain (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Increasingly dynamic organizational environments require organizations to adopt adaptive organizational designs to achieve their goals effectively. However, many organizations continue to implement organizational structures based on institutional traditions or legacy practices without considering their alignment with organizational strategies and environmental demands, resulting in overlapping authority, weak coordination, and limited adaptability. This condition highlights the need for a comprehensive conceptual study of organizational structure and anatomy as a foundation for effective organizational design and decision-making. This study aims to examine the concepts of organizational structure and anatomy, organizational structure models, organizational components, and organizational arrangement mechanisms to enhance organizational effectiveness. The study employed a qualitative approach using the library research method. Data were collected from books, scientific journal articles, and other relevant academic sources and analyzed through content analysis. The findings indicate that organizational effectiveness depends on the alignment between organizational design, strategic objectives, organizational size, and environmental conditions. Furthermore, leadership, communication, human resources, coordination, and organizational culture are identified as key supporting factors in implementing an effective organizational structure. In conclusion, adaptive organizational design and appropriate structural arrangements are essential prerequisites for improving organizational effectiveness, flexibility, and sustainability in responding to dynamic environmental changes. ABSTRAK Perubahan lingkungan organisasi yang semakin dinamis menuntut organisasi memiliki desain struktur yang adaptif untuk mendukung efektivitas pencapaian tujuan. Namun, berbagai organisasi masih menerapkan struktur berdasarkan kebiasaan atau warisan kelembagaan tanpa mempertimbangkan kesesuaiannya dengan strategi dan lingkungan, sehingga memunculkan tumpang tindih wewenang, lemahnya koordinasi, dan rendahnya kemampuan beradaptasi. Kondisi tersebut menunjukkan pentingnya kajian konseptual yang komprehensif mengenai struktur dan anatomi organisasi sebagai dasar pengambilan keputusan dalam desain organisasi. Penelitian ini bertujuan mengkaji konsep struktur dan anatomi organisasi, bentuk-bentuk struktur organisasi, komponen organisasi, serta mekanisme penataan organisasi untuk meningkatkan efektivitas organisasi. Penelitian menggunakan pendekatan kualitatif dengan metode kepustakaan (library research). Data diperoleh dari buku, artikel ilmiah, dan berbagai referensi akademik yang relevan, kemudian dianalisis menggunakan teknik analisis isi (content analysis). Hasil kajian menunjukkan bahwa efektivitas organisasi dipengaruhi oleh kesesuaian antara desain organisasi dengan tujuan, strategi, ukuran, dan lingkungan organisasi. Selain itu, kepemimpinan, komunikasi, sumber daya manusia, koordinasi, dan budaya organisasi menjadi faktor pendukung utama dalam implementasi struktur organisasi. Disimpulkan bahwa desain organisasi yang adaptif dan penataan struktur yang tepat merupakan prasyarat untuk meningkatkan efektivitas, fleksibilitas, dan keberlanjutan organisasi dalam menghadapi perubahan lingkungan.